Analysis of a novel magnetic stimulation system: Magnetic harmonic multi-cycle stimulation (MHMS) - Goetz, S.M.; Weyh, T.; Herzog, H.-G. (2009 International Conference on Biomedical and Pharmaceutical Engineering, 2009)
Magnetic stimulation is nowadays a standard instrument in research as well as clinical applications. But available systems still have some vital problems; these include the extreme energetic ineffectiveness and the poor flexibility of stimulation properties. In the following text we analyse a new degree of freedom for stimulation devices in the time domain. This approach owes its high potential from the simplicity to implement this feature in existing commercial systems. A similar principle has already been applied for a stimulation device long time ago, but was intentionally overdamped to mimic a monophasic system and therefore energetically meaningless. For the current work, the alternative design was implemented into a sophisticated simulation model to predict its properties. A substantial benefit is for instance the feasibility to lower the threshold of the required current within the stimulation coil for creating nervous action potentials dramatically. Accordingly, the energetic impact with its even quadratic relation to the amplitude and especially the reduction of the coil heating are remarkable. The opportunity to control the nervous reaction more precisely and to gain access to the field of more complex spiking patterns is another special attribute. The realization of the concept seems reasonably simple, whereas the impact was found to be enormous. But this shall not block the view of the fact that the discovery and the explanation needs a change of thinking about the stimulating effect of inductive stimulation.